2006
DOI: 10.1007/s11664-006-0093-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing on electrical properties of radio-frequency-sputtered ZnO films

Abstract: We report on the electrical properties of ZnO films and devices grown on different substrates by radio-frequency magnetron sputtering. The films grown on c-plane sapphire were annealed in the range 800-1,000°C. The electron concentration increased with annealing temperature reaching 1.4 3 10 19 cm -3 for 1,000°C. Mobility also increased, however, reaching its maximum value 64.4 cm 2 /V Á sec for 950°C anneal. High-performance Schottky diodes were fabricated on ZnO films grown on n-type 6H-SiC by depositing Au/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…We note that the current rectification ratio values achieved here exceed even those of ZnO Schottky diodes fabricated via vacuum-based techniques such as molecular beam epitaxy (MBE) and sputtering, for which typically values fall in the range of 10 3 –10 4 with the highest current rectification ratio of ∼10 5 reported for high-temperature-annealed sputtered ZnO Schottky diodes . Only devices fabricated on bulk single-crystal ZnO or on high-quality ZnO layers grown using pulsed laser deposition (PLD), demonstrate superior current rectification.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…We note that the current rectification ratio values achieved here exceed even those of ZnO Schottky diodes fabricated via vacuum-based techniques such as molecular beam epitaxy (MBE) and sputtering, for which typically values fall in the range of 10 3 –10 4 with the highest current rectification ratio of ∼10 5 reported for high-temperature-annealed sputtered ZnO Schottky diodes . Only devices fabricated on bulk single-crystal ZnO or on high-quality ZnO layers grown using pulsed laser deposition (PLD), demonstrate superior current rectification.…”
Section: Resultsmentioning
confidence: 73%
“…We note that the current rectification ratio values achieved here exceed even those of ZnO Schottky diodes fabricated via vacuum-based techniques such as molecular beam epitaxy (MBE) and sputtering, for which typically values fall in the range of 10 3 −10 431−35 with the highest current rectification ratio of ∼10 5 reported for high-temperature-annealed sputtered ZnO Schottky diodes. 36 Only devices fabricated on bulk singlecrystal ZnO or on high-quality ZnO layers grown using pulsed laser deposition (PLD), demonstrate superior current rectification. For example, Nakano et al 37 fabricated poly(3,4ethylenedioxythiophene):poly(styrenesulfonate) (PE-DOT:PSS) Schottky contacts on 0001 single-crystal ZnO with rectification ratios of 10 9 at ±2 V. Similarly, Allen et al 38 achieved current rectification values of up to 10 9 by depositing silver oxide Schottky contacts on the Zn polar surface of ZnO wafers, while Muller et al 39 reported a maximum rectification ratio value of 7 × 10 10 for Schottky diodes based on PLDgrown ZnO and sputtered PdOx contact.…”
Section: Resultsmentioning
confidence: 99%
“…A wide-bandgap n-type semiconductor ( ∼3. 1-3.4 eV) zinc oxide (ZnO) is an attractive material due to some important features such as good electrical and optical behaviors, direct band gap, and large exciton binding energy (60 meV) [1][2][3]. These features make ZnO an important material for optoelectronic applications, particularly in ultraviolet (UV) sensing applications [4][5][6].…”
Section: Introductionmentioning
confidence: 99%